SHARING BERSAMA DALAM ETIKA PENGGUNAAN SMARTPHONE UNTUK SISWA SEKOLAH DASAR - Tety Nur Cholifah; Dhea Ayu Selamita; Salsa Zania Isabella Agita; Nisa Lutfiana; Yulia Eka Yanti; Hendra Rustantono (Jurnal Edukasi Pengabdian Masyarakat, 2025)
This community service activity aims to improve elementary school students' understanding of smartphone ethics through an interactive and participatory approach. The program was implemented at SDN 2 Palaan, Ngajum District, Malang Regency, as part of the PPL program at Raden Rahmat Islamic University, Malang. The results showed an increase in students' understanding in three main aspects: ethics towards themselves, others, and the environment. Through the sharing method, students not only gained knowledge but also demonstrated positive behavioral changes in using technology wisely and responsibly.